(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses some aspects of the literary, historical and cultural heritage of Zahiriddin Muhammad Babur Kuragoni, a king and poet, a public and statesman, a skilled general. Also, in the assessment of Babur’s creativity, the work "Boburnoma" that shines like a diamond "Kuhi Nur" in a gold ring, and how the research and publication of this work is progressing in Uzbekistan and abroad will be given. Differences between original copies of works in manuscripts and ancient books belonging to the heritage of Babur Mirza in other countries are shown, and further work to be done in this regard is shown. The social importance of the decision taken by the President of the Republic of Uzbekistan to celebrate the 540th anniversary of the birth of the great poet and scientist, famous statesman Zahiriddin Muhammed Babur is emphasized.